Highly Sensitive Magnetic Array-based Platform for Neuronal Signal Recording. (2017) - Sharma, P.P.; Gervasoni, G.; Albisetti, E.; Moretti, D.; Baldelli, P.; Ferrari, G.; Sampietro, M.; Benfenati, F.; Bertacco, R.; Petti, D.
Abstract: This work presents a platform for the detection of the neuronal magnetic signal arising from the propagation of the action potential along the axon, via an array of highly sensitive magnetoresistive sensors and a low noise front-end electronic setup. We report the results of calculations and experiments for estimating the limit of detection of such platform in terms of minimum detectable magnetic field. Furthermore, an experimental setup for recording the magnetic signal in a brain slice is presented.